National identification as a mediator of mortality salience and culturally characteristic consumer behaviour. - Pooh, Karen Chuan Ling. (2011)
Past studies have addressed the impact of mortality salience (MS) on in-group identification (Castano, Yzerbyt, Paladino, & Sacchi, 2002) and materialism (Kasser & Sheldon, 2000) respectively. However, no existing research has combined the concepts of MS, in-group identification and materialism. Thus, this study utilizes a mediation model to examine national identification as a process that mediates the effect of MS on culturally characteristic